ON GENERALIZATIONS OF THE HILBERT NULLSTELLENSATZ FOR INFINITY DIMENSIONS (A SURVEY) - V.V. Kravtsiv (Vasyl Stefanyk Precarpathian National University, 2015)
The paper contains a proof of Hilbert Nullstellensatz for the polynomials on infinite-dimensional complex spaces and for a symmetric and a block-symmetric polynomials.